Pengusaha Tahu Desa Sumberejo Kulon Kecamatan Ngunut Kabupaten Tulungagung - Didik Priyo Sugiharto; Agussalim Ardiansyah (Jurnal ABM Mengabdi, 2016)
Small industries out an activity hereditary in some areas, especially in the village of Sumberejo Kulon District of Ngunut which is one of the small industrial centers out in Tulungagung. Small industrial tahu is a source of community income Sumberejo Kulon. The resulting tahu partner is kind of tofu or called out a vegetable. Business establishment knew aims to meet the needs of everyday life partner and future to create jobs is more socially Sumberejo Kulon Tulungagung in particular and society in general.The problems faced by partners related to the production process is the milling equipment soybeans that currently use the services of milled soya in neighboring partners to have to spend the cost for the services of milling, cooking utensils soybeans that have been less feasible for cooking, where production is less clean, and excellent knowledge limited regarding bookkeeping and marketing management. IbM Program (science and technology to the Community) will be able to solve the problems faced by partners that will create greater business tahu and efficiently so that the future will be able to strengthen the national economy.